2014
DOI: 10.1016/j.rmed.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in idiopathic pulmonary fibrosis: A meta-analysis from placebo controlled trials

Abstract: Mortality is heterogeneous and dependent on entry criteria. Infection rates were high, both with and without immunosuppression, and were higher in severe disease. Consideration should be given to alternative outcomes to mortality in future IPF trials if severe disease is excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 36 publications
2
43
0
2
Order By: Relevance
“…This study confirmed the predictive value of absolute baseline FVC or %pFVC, which has been consistently shown in the literature . This finding suggested that acute exacerbations are more likely to occur in patients with more advanced disease, and a similar conclusion was drawn from a meta‐analysis of placebo‐controlled trials that acute exacerbations were less commonly observed in trials that excluded severe disease than those that did not . The parameter %pDL CO was shown to be a significant predictor of acute exacerbations in some studies, although this finding was not confirmed in several other reports .…”
Section: Discussionsupporting
confidence: 81%
“…This study confirmed the predictive value of absolute baseline FVC or %pFVC, which has been consistently shown in the literature . This finding suggested that acute exacerbations are more likely to occur in patients with more advanced disease, and a similar conclusion was drawn from a meta‐analysis of placebo‐controlled trials that acute exacerbations were less commonly observed in trials that excluded severe disease than those that did not . The parameter %pDL CO was shown to be a significant predictor of acute exacerbations in some studies, although this finding was not confirmed in several other reports .…”
Section: Discussionsupporting
confidence: 81%
“…The study was thereafter aborted for ethical reasons related to this difference [7]. Because the frequency of AE-IPF has been reported to be influenced by disease severity [23], differences in the eligibility criteria or patient population in these studies are a possible explanation for the discrepancy. Further studies are needed to clarify the ability of pirfenidone to prevent AE-IPF.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, this occurred with a frequency of 41 cases per 1000 patient-years [11]. HRCT is often obtained in the work-up of IPF patients with acute symptoms.…”
Section: Usual Interstitial Pneumoniamentioning
confidence: 99%